Increasing the Reliability of the Competitive Activity of Highly Qualified Wrestlers - Karimov Bekzod Boyqobilovich; Normurodov Ulugbek Meylievich (Genius Journals, 2022)
The paper deals with the issues of improving the reliability of the competitive activity of highly qualified wrestlers. Various methods for improving the technical and tactical actions of wrestlers used in competitive fights are proposed. The article is intended for coaches working with highly qualified athletes in various types of wrestling.
Keywords: Competition; wrestlers; technique; tactics; reliability of competitive activity